Words that hurt: Why mental health stigma is often vilification, and requires legal protection. (March 2023) - Katterl, Simon
Despite a series of education programs and initiatives, mental health stigma persists across the community. This is due, in part, to the law's silence on whether mental health stigma should be considered vilification. This article analyses current Australian anti-discrimination and anti-vilification protections, finding that the latter needs enhancing to include protections against mental health vilification.